Novel Strategy to Drive the Intracellular Uptake of Lipid Nanoparticles for Photodynamic Therapy. (13th March 2023) - Ho, Tiffany; Guidolin, Keegan; Makky, Ali; Valic, Michael; Ding, Lili; Bu, Jiachuan; Zheng, Mark; Cheng, Miffy H. Y.; Yau, Jeremy; Chen, Juan; Zheng, Gang
Abstract: Nanoparticles' uptake by cancer cells upon reaching the tumor microenvironment is often the rate‐limiting step in cancer nanomedicine. Herein, we report that the inclusion of aminopolycarboxylic acid conjugated lipids, such as EDTA‐ or DTPA‐hexadecylamide lipids in liposome‐like porphyrin nanoparticles (PS) enhanced their intracellular uptake by 25‐fold, which was attributed to these lipids' ability to fluidize the cell membrane in a detergent‐like manner rather than by metal chelation of EDTA or DTPA. EDTA‐lipid‐incorporated‐PS (ePS) take advantage of its unique active uptake mechanism to achieve >95 % photodynamic therapy (PDT) cell killing compared to <5 % cell killing by PS. In multiple tumor models, ePS demonstrated fast fluorescence‐enabled tumor delineation within minutes post‐injection and increased PDT potency (100 % survival rate) compared to PS (60 %). This study offers a new nanoparticle cellular uptake strategy to overcome challenges associated with conventional drug delivery. Abstract : We herein report a novel aminopolycarboxylic acid lipid‐embedded porphyrin nanoparticle and elucidated its unique cellular delivery mechanism that affords its enhanced intracellular uptake, fast fluorescence activation, and superior photodynamic therapeutic (PDT) efficacy. By exploiting this enhanced delivery strategy, we might overcome challenges associated with intracellular drug delivery to advance therapeutic outcomes.